STRATEGI PROMOSI PENJUALAN ENTRANCE TICKET DALAM KONDISI LOW SEASON DI PURA LUHUR ULUWATU - Suryani Samosir, Nova Irma; Mahadewi, NPE.; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024), 2024)
In times of low season, the number of tourist visits to Pura Luhur Uluwatu experiences consistent fluctuations predominantly characterized by a year-on-year decline. Effective promotional strategies can enhance awareness of Pura Luhur Uluwatu among tourists, even during non-peak periods. The objective of this research is to determine the appropriate promotional strategies by analyzing the strengths and weaknesses of internal factors, as well as the opportunities and threats posed by external factors. Data for this study were gathered through observations, interviews, documentation, and a review of relevant literature. The data analysis involved a qualitative descriptive approach and a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats).The findings of this research elucidate that the promotional strategy at Pura Luhur Uluwatu encompasses a combination of advertising and Public Relations. The strategies formulated within the SWOT analysis include leveraging technology to showcase the scenic beauty, utilizing technology for public relations, provide training to working staff, offering discounts through social media, marketing the temple on online booking platforms, and providing special promotions for online bookings. With these results, this conceptual framework can serve as a reference for the management of Pura Luhur Uluwatu to develop more effective strategies in addressing challenges and capitalizing on identified opportunities. It can also aid in planning concrete steps to enhance the visitor experience, optimize human resource utilization, and ensure operational sustainability during the low season.